Wirkung phonetischer Parameter des Deutschen auf nichtdeutsche Muttersprachler*innen - Skoczek, Robert (Neofilolog, 2021)
<span class="NormalTextRun SCXW62052560 BCX0" data-ccp-parastyle="Standard" data-ccp-parastyle-defn="{"ObjectId":"4c303603-9c91-4d6b-8201-1966ca06893b|87","ClassId":1073872969,"Properties":[134224948,"false",134233614,"true",134234082,"true",201340122,"2",201341983,"0",268442635,"22",335551500,"4278190080",335551547,"1045",335551550,"1",335551620,"1",335559704,"1025",335559705,"1033",335559738,"0",335559739,"160",335559740,"259",469775450,"Standard",469778129,"Standard",469778325,"[\"Heading 3\",\"Indeks\",\"Nagłówek1\",\"caption\",\"Text body\",\"Normal (Web)\",\"List Paragraph\",\"annotation text\",\"Balloon Text\"]"]}">This paper tries to answer the question which phonetic parameters are particularly responsible for the sound of German. In particular, the accent-rhythmic structures are discussed. In doing so, we reflect on which factors also shape attitudes and perception of German.